2020
DOI: 10.1002/rsa.20945
|View full text |Cite
|
Sign up to set email alerts
|

Coloring triangle‐free graphs with local list sizes

Abstract: We prove two distinct and natural refinements of a recent breakthrough result of Molloy (and a follow‐up work of Bernshteyn) on the (list) chromatic number of triangle‐free graphs. In both our results, we permit the amount of color made available to vertices of lower degree to be accordingly lower. One result concerns list coloring and correspondence coloring, while the other concerns fractional coloring. Our proof of the second illustrates the use of the hard‐core model to prove a Johansson‐type result, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…In Section 5, we give some indication that our application of this analysis is essentially tight. The same method was used for similar results specific to triangle-free graphs [8,10]; to an extent, the present work generalises that earlier work.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…In Section 5, we give some indication that our application of this analysis is essentially tight. The same method was used for similar results specific to triangle-free graphs [8,10]; to an extent, the present work generalises that earlier work.…”
supporting
confidence: 62%
“…is a lower bound on the size of a largest independent set in G. We have presented in an earlier work [8,Lemma 3] how to construct a fractional colouring of a graph G using a probability distribution over the independent sets of any induced subgraph H of G. Informally speaking, if this probability distribution has the property that for every vertex ∈ v H, either v has a good chance of belonging to the corresponding random independent set I, or the expected number of neighbours of v in I is large, then we obtain an upper bound on χ G ( )…”
Section: Notation and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same subset of the present authors with Davies [5] have found a surprisingly short proof for the fractional colouring analogue of Theorem 4.5, via elementary properties of the hard-core model. Using this, there is a streamlined, self-contained proof (of about two pages overall) of Theorem 1.4.…”
Section: Notes Addedmentioning
confidence: 59%
“…Since the posting of our manuscript to arXiv, the second half of our paper has precipitated a number of significant further developments. [13] has improved the asymptotic leading constant to 2 in Theorem 3.5.…”
Section: Acknowledgementsmentioning
confidence: 98%